A Study on Nano Catalysis and Its Applications: Exploring the Role of Nanoparticles in Catalytic Reactions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study has been attempted to know about the nanocatalysis and its applications. Catalysis is the process by which chemical reaction rates are altered by the addition of a substance (the catalyst) that is not itself changed during the chemical reaction. Catalysts are usually used so that chemical reactions can occur at temperatures and pressures low enough for producers to use economically priced equipment or to ensure that the rate of production of a desired product is greater than the rates of production of undesirable byproduct. Nanocatalysis has long become an important part of nanoscience. Nanoparticle can substitute conventional material and serve as active and stable heterogeneous catalysts or as support material for various catalytic groups.